2022
DOI: 10.3390/vetsci9110647
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphology and Chemical Constituents of Interdigital Gland of Vembur Sheep, Ovis aries

Abstract: The interdigital gland is a specialized skin gland located between the digits of Artiodactyla (i.e., even-toed ungulates). Its secretion participates in semiochemical communication, and protects from ultraviolet radiation as well as fungal and bacterial infection of the feet. The present study aimed at finding if there are male-female differences in the anatomy, morphology, and volatile compounds of the interdigital gland of the South Indian breed of Vembur sheep. A total of 24 sheep (12 each of male and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…The histology of the interdigital sinus consisted of a fibrous capsule, epidermis and dermis layers from the outside to the inside following the results of studies conducted in Tuj (Aslan et al., 2010 ), Akkaraman (İlgün et al., 2022 ), Barbados black belly (Mohamed and Adogwa, 2016 ) and Egyptian (Awaad et al., 2015 ) native sheep. Similar to the study in Vembur sheep (Rajagopal et al., 2022 ), the epidermis layer was composed of stratified squamous epithelium. It has been reported that the interdigital gland in ovine animals has a sweat gland component with dual secretory activity (Pourlis, 2010 ).…”
Section: Discussionsupporting
confidence: 79%
“…The histology of the interdigital sinus consisted of a fibrous capsule, epidermis and dermis layers from the outside to the inside following the results of studies conducted in Tuj (Aslan et al., 2010 ), Akkaraman (İlgün et al., 2022 ), Barbados black belly (Mohamed and Adogwa, 2016 ) and Egyptian (Awaad et al., 2015 ) native sheep. Similar to the study in Vembur sheep (Rajagopal et al., 2022 ), the epidermis layer was composed of stratified squamous epithelium. It has been reported that the interdigital gland in ovine animals has a sweat gland component with dual secretory activity (Pourlis, 2010 ).…”
Section: Discussionsupporting
confidence: 79%